PTU-121 Llt1 Is Upregulated In Hepatocellular Carcinoma And Inhibits Nk Cell Cytotoxicity. (9th June 2014) - Kumar, N; Mroz, A; Aletrari, M; Goldin, R; Purbhoo, M
Abstract : Introduction: Liver cancer is on the rise and prognosis is poor partly due to late diagnosis and a lack of systemic chemotherapy. Identification of novel markers allowing early diagnosis of hepatocellular carcinoma (HCC) and to act as targets for immunotherapies is essential to kerb rising mortality. Lectin-like transcript 1(LLT1) interacts with CD161, 1 a receptor expressed on almost all NK cells. For the first time, we investigate the expression of LLT1 in the liver and HCC, both in vivo and in vitro, and determine the effect of LLT1 on NK cell function. Methods: LLT1 expression in vivo was determined by immunohistochemistry comparing 10 HCC specimens (resections and biopsies) to 15 normal liver controls. In vitro expression was demonstrated using flow cytometry to review HCC cell lines (Huh7, HepG2). Peripheral blood mononuclear cells (PBMCs), including NK cells, from healthy donors were incubated with target cells expressing different levels of LLT1:Huh7 cells, Huh7 cells expressing increased levels of LLT1(achieved by transfection), and Jurkat cells lacking LLT1. The effect of these incubations on CD161 + and CD161-NK cell cytotoxicity was assessed by measuring CD107a expression using flow cytometry. This assay was performed in triplicate using 2 different donors on 3 separate occasions. Statistical analysis of variance (ANOVA) was performed to assess differences in NK cell cytotoxicity between each incubation condition. Results: Hepatocytes in normal and cirrhotic liver do not express LLT1. However, LLT1 is extensively upregulated in HCC in vivo with strong, diffuse staining in 9 out of 10 cases, and more focal staining seen in the remaining case. LLT1 is expressed in vitro on HCC cell lines (Huh7 and HepG2). CD161 + NK cells show reduced cytotoxicity, compared to CD161-NK cells, when incubated with Huh7 cells expressing LLT1. Incubation with Huh7 cells correlates with significantly reduced activity by CD161 + NK cells (p ≤ 0.001) when compared to CD161 + NK cell activity against non-LLT1 expressing Jurkat cells. CD161 + NK cell cytotoxicity is further reduced when incubated with Huh7 cells expressing increased LLT1 levels (as achieved by transfection; p ≤ 0.05 when compared to CD161 + NK cell activity when incubated with non-transfected Huh7 cells). In contrast, the activity of CD161 + and CD161-NK cells is not significantly different when the target cell does not express LLT1(Jurkat cell). Conclusion: We demonstrate for the first time that LLT1 is not expressed by normal liver tissue, but upregulated in HCC. LLT1 inhibits NK cell cytotoxicity, representing a possible mechanism for HCC to evade the immune response to cancer. Therefore, not only may LLT1 be used as a diagnostic marker for HCC, it represents a novel immunotherapy target. Reference: Aldemir et al. Cutting edge: LLT1 is a ligand for the CD161 receptor. J immunol 2005:7791 Disclosure of Interest: None Declared.